Peripheral eco‐morphology predicts restricted lineage diversification and endemism among corvoid passerine birds. Issue 1 (8th November 2020) - Kennedy, Jonathan D.; Marki, Petter Z.; Fjeldså, Jon; Rahbek, Carsten
Abstract: Aim: Across a variety of taxonomic scales, species diversity is unevenly distributed among its constituent units, and clades with few species are more common than expected assuming homogeneous rates of speciation and extinction among lineages. In order to explain the prevalence of species‐poor families among a global and species‐rich radiation of passerine birds, we test whether these groups share common eco‐morphological, geographical and phylogenetic attributes. Location: Global. Time period: Late Oligocene to the present day. Major taxa studied: The Corvides ( c . 790 species). Methods: We obtained 10 linear measurements of external morphology for 782 species of corvoid passerines. Using these measurements as a proxy for species ecology, we assessed the positioning of corvoid families in eco‐morphological trait space and how these factors were associated with their species richness and rates of lineage diversification. Subsequently, we compared these same characteristics (species richness, morphological positioning and rates of lineage diversification) between families that are currently endemic to the Australasian ancestral area of the Corvides with those that have dispersed and diversified throughout other continental and insular landmasses. Results: Families with low species richness and rates of diversification tend to occupy the most peripheral positions in eco‐morphological trait space, with almost all of these groups being endemic to Australasia. The peripheral eco‐morphological positioning of the Australasian groupings is generally greater than expected upon accounting for differences in phylogenetic isolation and heterogeneity in rates of trait evolution, implying that species‐poor corvoid families repeatedly evolved towards marginal areas of morphospace. Main conclusions: The over‐representation of species‐poor clades across diverse sets of organismal groups is consistent with their evolution towards, and the maintenance in, marginal areas of ecological niche space. The evolution of peripheral eco‐morphological characters represents a potentially significant limit to rates of range expansion and lineage diversification.